A multi-channel interactive learning model of social innovation - Attila Havas; György Molnár (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We develop a new model of social innovation (SI) inspired by the multi-channel interactive learning model of business innovation. As opposed to the linear models of innovation, this model does not identify 'stages' of business innovation. Rather, it stresses that innovation is an interactive process, in which collaboration among various partners are crucial, as they possess different types of knowledge, all indispensable for successful innovation activities. Having considered numerous definitions of SI, first we propose a new one, then adapt the multi-channel interactive learning model to SI. To do so, we identify the major actors in an SI process, their activities, interactions, modes of (co-)producing, disseminating and utilising knowledge. We also consider the micro and macro environment of a given SI. We illustrate the analytical relevance of the proposed model by considering three real-life cases. The model can assist SI policy-makers, policy analysts, as well as practitioners when devising, implementing or assessing SI.
Keywords: O35; O30; J71; G21; L31; O18; 330; Definitions and models of social innovation; Business innovation studies; Multi-channel interactive learning; Microcredit industry; Roma minority; Social housing